1997
DOI: 10.1083/jcb.138.5.1169
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of L-selectin Tethers and the Mechanics of Selectin-mediated Rolling

Abstract: Two mechanisms have been proposed for regulating rolling velocities on selectins. These are (a) the intrinsic kinetics of bond dissociation, and (b) the reactive compliance, i.e., the susceptibility of the bond dissociation reaction to applied force. To determine which of these mechanisms explains the 7.5–11.5-fold faster rolling of leukocytes on L-selectin than on E- and P-selectins, we have compared the three selectins by examining the dissociation of transient tethers. We find that the intrinsic kinetics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

56
416
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(475 citation statements)
references
References 55 publications
(104 reference statements)
56
416
3
Order By: Relevance
“…With the use of flow chambers, several groups have shown that lifetimes of tethers of PSGL-1-expressing cells to P-selectin-coated surfaces decreased with increasing wall shear stress, which is consistent with slip bond behaviour 7,9,[11][12][13] . These experiments were conducted at wall shear stresses ranging from 0.17 to 3.0 dyn cm 22 , corresponding to tether forces of 20-400 pN.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…With the use of flow chambers, several groups have shown that lifetimes of tethers of PSGL-1-expressing cells to P-selectin-coated surfaces decreased with increasing wall shear stress, which is consistent with slip bond behaviour 7,9,[11][12][13] . These experiments were conducted at wall shear stresses ranging from 0.17 to 3.0 dyn cm 22 , corresponding to tether forces of 20-400 pN.…”
mentioning
confidence: 66%
“…It has been suggested that force could either shorten bond lifetimes, because work done by the force could lower the energy barrier between the bound and free states 4 ('slip'), or prolong bond lifetimes by deforming the molecules such that they lock more tightly 5,6 ('catch'). Whereas slip bonds have been widely observed [7][8][9][10][11][12][13][14] , catch bonds have not been demonstrated experimentally. Here, using atomic force microscopy and flow-chamber experiments, we show that increasing force first prolonged and then shortened the lifetimes of P-selectin complexes with P-selectin glycoprotein ligand-1, revealing both catch and slip bond behaviour.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28][29] Both selectin-and glycoprotein Ib␣-binding have been shown to have a shear threshold dependence whereby resistance to detachment increases proportional to increasing shear. These shear requirements are important not only for adhesion promotion but also maintenance.…”
Section: Discussionmentioning
confidence: 99%